Effects of historical nostalgia intensity on consumer behaviour - Marchegiani, Christopher; Phau, Ian (School of Marketing, Curtin Business School, 2008)
This paper compares the effect of high, medium and low levels of historical nostalgic reactions in consumers exposed to a historical nostalgic advert on cognitive, attitudinal, and purchase intension reactions. These important consumer reactions are found to be effected in some way due to the change in historical nostalgia intensity. Although nostalgia has been explored in the past, effects of historical nostalgia specifically are generally unexplored. This paper begins to fill this important empirical gap.